What we wanted, where it led us and what happened afterwards: Serbia at the PQ 2015. Issue 1 (2nd April 2016) - Dadić Dinulović, Tatjana
ABSTRACT: At the Prague Quadrennial of Performance Design and Space 2015 (PQ 2015) Serbia showcased the work entitled Process which was thematically, methodologically and spatially unified for both selection categories – the Section of Countries and Regions and the Students' Section. Inspired by the phenomenon of 'politics' and the idea of 'process', the work represented the result of a research and creative process lasting for several months, throughout which the structure of the piece was gradually built and defined at all levels, staying open for further developments and interpretations until the final encounter with the public and space in Prague. The creative team consisted of 46 students, artists and curators, coming from different educational backgrounds, artistic disciplines and institutions. The work, for which Serbia's team was awarded the Gold Medal PQ 2015 for 'Provoking а Dialogue', concludes a 20-year period during which scene design as an interdisciplinary field has been established in Serbia, introduced into the education system and formally recognised.